PROTOTIPE PERANGKAT NOTIFIKASI UNTUK SMARTPHONE BERBASIS ARDUINO PRO MICRO - Asep Saefullah; Mochamad Ibnu Safari; Handri Samanta (CCIT Journal, 2015)
The widespread use of smartphones in all societies make increasing demands of smartphone accessories tools for ease of its use in everyday life. As if the user is in public, attending a meeting, or are driving a motor vehicle. Apart from the rapid use of smartphone technology on society, there is also the technology in the field of microcontroller that can be said to be rapid development in people's daily life, namely that a module arduino microcontroller. Therefore, we need a microcontroller-based devices that can help the user to display the condition of smartphones such as the presence of incoming messages or incoming calls to the smartphone, small size and can be implemented in accordance with the user's work. By using prototypes in the process of designing a simple model that can represent the actual future results and methods of the blackbox for testing this tool to determine whether the software and hardware to work properly and has been as expected. Can produce a device that functions as a media notification for smartphones such as short messages and incoming calls, and has an interface OLED Display. It can help users Smartphone in everyday life.